An examination of the satiric vision of Ahmadou Kourouma in 'Waiting for the wild beasts to vote' - Ndlovu, Isaac (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA) -- University of Stellenbosch, 2008.